A Case of El Duende: Art-Based Supervision in Addiction Treatment. Issue 3 (3rd July 2021) - Chilton, Gioia; Lynskey, Kristin; Ohnstad, Erica; Manders, Elizabeth
Abstract: Addictions professionals are at risk for compassion fatigue and secondary traumatic stress. This arts-based research, enhanced with qualitative processes, explored the experience and benefits of El Duende process painting (EDPP) in clinical supervision with art therapists. Supervision consisted of eight sessions. Data included interviews and photographs taken of the EDPP process. Findings demonstrated that EDPP art therapy supervision was a space for integrative transformation. It promoted a psychologically safe place to cope with compassion fatigue and process secondary traumatic stress.